THE IMPLEMENTATION OF BLENDED LEARNING MODEL IN IMPROVING STUDENTS?? LISTENING COMPREHENSION - Husni Mubarok (Universitas Islam Nahdlatul Ulama Jepara, 2015)
This study was aimed at 1) finding out how Blended Learning model was implemented to improve students?? comprehension, 2) finding out how Blended Learning model could improve students?? listening comprehension,3) finding out students response toward the implementation of Blended Learning in Listening class. The subject of this study was the second semester students of English Education Program (PBI) of Islamic University of Nahdlatul Ulama` (UNISNU) Jepara. The research design of this study was a classroom action research. The instruments of this study were observation, interview, questionnaire, and Listening test. This study consists of three cycles and each cycle consists of two meetings. The findings show that Blended Learning could be implemented in two kinds of model; Flip model and Lab Rotation model. In Flip model, students did the activity in their homes via online which was not done in classroom and got re-statement from lecturer in the classroom, while in Lab Rotation model, students are divided into three groups; getting lecturing from lecturer, discussing with friends and doing online activity. Blended learning model could improve students?? comprehension in Listening class. It was proved with students?? final score in Listening was higher than passing grade. It was 77. Students had positive view toward the implementation of Blended Learning model in Listening class. Keywords: blended learning, listening, comprehension.Penelitian ini bertujuan untuk 1) membahas bagaimana Blended Learning diterapkan untuk meningkatkan pemahaman mahasiswa, 2) membahas bagaimana bagaimana Blended Learning dapat meningkatkan pemahaman listening mahasiswa, 3) mengetahui respon siswa terhadap penerapan Blended Learning dalam kelas listening. Subjek penelitian ini adalah mahasiswa semester dua prodi Pendidikan Bahasa Inggris UNISNU Jepara. Desain penelitian ini adalah penelitian tindakan kelas. Instrument yang digunakan adalah observasi, interview, kuesioner, dan tes listening. Penelitian ini terdiri dari dua siklus, dan tiap siklus terdiri dari dua pertemuan. Hasil penelitiannya adalah terdapat dua jenis Blended Learning; flip model dan lab rotation model. Dalam flip model, mahasiswa melakukan aktifitas online ketika dirumah apa yang tidak dibahas didalam kelas, dan mendapatkan penguatan ketika didalam kelas. Sementara lab rotation model, siswa dibagi dalam tiga kelompok; tatap muka dengan dosen, diskusi teman, dan kegiatan online. Blended Learning dapat meningkatkan pemahaman mahasiswa dalam kelas listening. Itu dibuktikan dengan nilai akhir yang lebih tinggi dari nilai ketuntasan minimal (77). Mahasiswa memiliki pandangan positif terkait penerapan blended learning dalam kelas listening. Keywords: blended learning, listening, comprehension